Understanding the combined symptom medication score in the light of contexts and mechanisms - Anne Møller Lohmann; Anne Poder Petersen; Johannes Martin Schmid; Hans Jürgen Hoffmann; Jeanette Finderup (PLoS ONE, 2025)
Background In a clinical trial of allergen‐specific immunotherapy for allergic rhinoconjunctivitis, the Combined Symptom Medication Score (CSMS) was utilized as the primary endpoint. This was aligned with the European Academy of Allergy and Clinical Immunology recommendation. However, participants wanted to elaborate on how their behaviour affected their score, so voluntary free text boxes were added to the CSMS questionnaire. This study aimed to evaluate the patient-reported outcomes registered in the free text boxes to identify and understand contexts and mechanisms that may affect the CSMS. Methods The realist evaluation methodology was followed in four iterative steps: 1) development of the initial programme theory and context-mechanism-outcome (CMO) configurations, 2) collection of evidence, 3) data analysis, and 4) interpretation and assessment of results. Results Seven CMO configurations were identified, highlighting contexts and mechanisms that may affect the CSMS. These included CMO1 – decision on preventive relief medication dosage, CMO2 – exhibiting symptom-relieving behaviour, CMO3 – being exposed to different levels of grass pollen, CMO4 – mistaking other symptoms for grass pollen-induced symptoms, CMO5 – different exposure to grass pollen when travelling abroad, CMO6 – reporting of relief medication for other allergies in CSMS, and CMO7 – failure to report symptoms not included in CSMS. Conclusion This realist evaluation contributes verified CMO configurations based on patient perspectives to understand how context and mechanisms may affect the CSMS. We recommend further investigation in quantitative studies, as awareness of these CMOs may increase the internal validity of future allergy trials using CSMS as an endpoint. Trial registration ILIT.NU: EudraCT 2020-001060-28.